Risk Factors for Measles in HIV-infected Children and Adolescents in Botswana. Issue 10 (October 2015) - Wirth, Kathleen E.; Wolf, Elizabeth R.; Goldfarb, David M.; Ho-Foster, Ari; Tolle, Michael; Jacovides, Christina; Kirk, Brianna; Chise, Mamiki; Steenhoff, Andrew P.
Abstract : We conducted a matched case-control study of 566 HIV-infected children in Botswana during a 2009–2010 measles outbreak to identify the risk factors for measles. Children in the oldest age quartile (≥13.1 years) were 4-fold more likely to acquire measles than those in the youngest quartile (<7.1 years). HIV-infected older children and adolescents may benefit from additional measles vaccination.